Process design and multi-objective optimization for separation of ternary mixtures with double azeotropes via integrated quasi-continuous pressure-swing batch distillation - Zhao, Fei; Xu, Zaifeng; Zhao, Jiangang; Wang, Jia; Hu, Mingyue; Li, Xin; Zhu, Zhaoyou; Cui, Peizhe; Wang, Yinglong; Ma, Yixin (Separation and purification technology, 2021)
•Ternary mixture with double azeotropes was separated by pressure-swing batch distillation.•Integrated quasi-continuous triple-column process was further proposed and analyzed.•Multi-objective optimization algorithm was adopted to realize the optimization of process.•Thermal integration technology was used to further reduce energy consumption. An multivessel double-column pressure-swing batch distillation process and a triple-column integrated quasi-continuous distillation process were designed to separate ternary mixtures with double azeotropes of ethyl acetate-methanol-water. The process feasibility was analyzed based on ternary phase diagram. Based on a production capacity of 100 kmol/batch, the corresponding control strategy was proposed to achieve the effective separation of the mixture. Taking the minimum total annual cost as the objective function, the process parameters of the double-column process were optimized to determine the optimal operating pressure. Exergy loss of distillation column was calculated to evaluate the thermodynamic performance of the process. To further improve the separation efficiency of the process, a third column was integrated in the double-column batch distillation process to separate the methanol-water mixture directly. Combined with sequential iterative optimization sequence and multi-objective optimization algorithm, the triple-column process parameters were optimized, and the trade-off between equipment cost and carbon dioxide was realized. Thermal integration technology was adopted to further reduce the energy consumption of the triple-column process. The results show that the carbon dioxide emissions and total annual cost of the double-column process are 1.323 × 106 kg/y and 2.107 × 105 $/y. The purity of ethyl acetate and water was 99.9 mol%. While the purity of methanol was 99.5 mol%. The total annual cost and emission of the triple-column process were 1.993% and 1.890% higher than that of the double-column process, respectively, but the methanol purity was further improved to 99.9 mol%. Compared with the double-column process, the total annual cost and carbon dioxide emissions of the triple-column process with thermal integration technology were reduced by 1.281% and 17.337%.